2018
DOI: 10.1155/2018/9698710
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Urban Particulate Matter by Diffusive Gradients in Thin Film Technique

Abstract: A diffusive gradient in thin films (DGT) technique was employed in characterization of the particulate matter related to the urban area suffering from heavy traffic. Kinetics of mobilization metals fluxes from the metal-contaminated particulate matter was investigated. To monitor responses of the particulate matter sample, DGT probes of various thickness of diffusion layer were deployed in aqueous model suspensions of the particulate matter for different time periods. Particulate matter samples and exposed DGT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The kinetic data obtained during the experiments can be fitted by a suitable equation. Some of the previous papers regarding leaching kinetics from PM did not treat their data, but they only verified the leaching times (Hsu et al, 2005;Armiento et al, 2013) or showed the applicability of a new method (diffusive gradients in thin film) for the analysis of PM (Dufka and Dočekal, 2018). In the other papers, it was considered that the leaching rate determining step was the solubilisation from the PM surface, so that a first order kinetic law should apply (Desboeufs et al, 1999;Joshi et al, 2009;Huang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The kinetic data obtained during the experiments can be fitted by a suitable equation. Some of the previous papers regarding leaching kinetics from PM did not treat their data, but they only verified the leaching times (Hsu et al, 2005;Armiento et al, 2013) or showed the applicability of a new method (diffusive gradients in thin film) for the analysis of PM (Dufka and Dočekal, 2018). In the other papers, it was considered that the leaching rate determining step was the solubilisation from the PM surface, so that a first order kinetic law should apply (Desboeufs et al, 1999;Joshi et al, 2009;Huang et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Another information which has been sought in the literature, even if much less often than equilibrium solubility, was the kinetics of the solubilisation process (Desboeufs et al, 1999;Desboeufs et al, 2005;Hsu et al, 2005;Joshi et al, 2009;Armiento et al, 2013;Huang et al, 2016;Dufka and Dočekal, 2018). The rate by which a given element is released from the PM can be as relevant as the solubility at equilibrium, because this data would allow to model also the timing of the releasing process, especially when the contact between PM and aqueous phase does not last for long times.…”
Section: Introductionmentioning
confidence: 99%
“…Air pollutants also increased the incidence of various gastrointestinal diseases and liver fibrosis and increased the morbidity and mortality of lung cancer and cardiovascular diseases, making PM a threat to human health 3,4 . Numerous hazardous components in PM are known to contain various toxins such as carbonaceous cores, polycyclic aromatic hydrocarbons (PAHs), quinones, sulfate, heavy metals, and endotoxins, which are typically accompanied by decreased visibility 5 . Based on its aerodynamic diameter, PM is crudely categorized as coarse PM, which has an aerodynamic diameter of 2.5–10 μm; fine PM, which has an aerodynamic diameter <2.5 μm; and ultrafine PM (UFPM), which has an aerodynamic diameter <0.1 μm.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies to understand the reason for such variations would be welcomed. The first use of DGT for assessing the biocharacteristics of airborne particulates involved 25 preparing polyacrylamide hydrogels embedded with Chelex 100 ion-exchange resin and immersing them in simulant dust suspensions for various time intervals. Upon removal, the probes were digested in a HNO 3 -HCl (4+1) acid mixture using MAD and analysed by ICP-MS to determine the labile metal content released from these dusts.…”
Section: Sample Preparationmentioning
confidence: 99%